PENGARUH PROMOSI MELALUI MEDIA SOSIAL TERH ADAP REPURCHASE INTENTION MELALUI ELECTRONIC WORD OF MOUTH - Savitri, Eka Ayu (JURNAL ILMU MANAJEMEN UNIVERSITAS TADULAKO, 2016)
This study aims to identify and analyze: (1) direct influence of promotion via social media on eWOM at RM Radja Penyet Mas Fais in Palu, (2) direct influence of promotion via social media on repurchase intention at RM Radja Penyet Mas Fais in Palu, (3) direct influence of eWOM to repurchase intention on RM Radja Penyet Mas Fais in Palu. Type of research is quantitative. The population consists of people who have been exposed information about RM Radja Penyet Mas Fais in social media, and had visited RM Radja Penyet Mas Fais or become followers @radjapenyetmasfais instagram. Sampling technique is purposive sampling, with total sample of 100 respondents. Data collecting method using online and offline questionnaires that have been tested for their validity and reliability. The analytical method using path analysis. The results show that: (1) there is direct influence of promotion via social media on eWOM at RM Radja Penyet Mas Fais in Palu, (2) there is direct influence of promotion via social media on repurchase intention at RM Radja Penyet Mas Fais in Palu, (3) there is no direct influence of eWOM on repurchase intention at RM Radja Penyet Mas Fais in Palu.